Relationship Between Intraoperative Electrocochleography and Hearing Preservation. Issue 1 (January 2022) - Lenarz, Thomas; Buechner, Andreas; Gantz, Bruce; Hansen, Marlan; Tejani, Viral D.; Labadie, Robert; O'Connell, Brendan; Buchman, Craig Alan; Valenzuela, Carla V.; Adunka, Oliver F.; Harris, Michael S.; Riggs, William J.; et al.
Abstract : Objectives: To compare intraoperative intracochlear electrocochleography (ECochG) with hearing preservation outcomes in cochlear implant (CI) subjects. Design: Intraoperative electrocochleography was performed in adult CI subjects who were recipients of Advanced Bionics' Bionics LLC precurved HiFocus MidScala or straight HiFocus SlimJ electrode arrays. ECochG responses were recorded from the most apical electrode contact during insertion. No changes to the insertions were made due to ECochG monitoring. No information about insertion resistance was collected. ECochG drops were estimated as the change in amplitude from peak (defined as maximum amplitude response) to drop (largest drop) point after the peak during insertion was measured following the peak response. Audiometric thresholds from each subject were obtained before and approximately 1 month after CI surgery. The change in pure tone average for frequencies between 125 Hz and 500 Hz was measured after surgery. No postoperative CT scans were collected as part of this study. Results: A total of 68 subjects from five surgical centers participated in the study. The study sample included 30 MidScala and 38 SlimJ electrodes implanted by approximately 20 surgeons who contributed to the study. Although a wide range of results were observed, there was a moderate positive correlation (Pearson Correlation coefficient, r = 0.56, p < 0.01) between the size of the ECochG drop and the magnitude of pure tone average change. This trend was present for both the MidScala and SlimJ arrays. The SlimJ and MidScala arrays produced significantly different hearing loss after surgery. Conclusion: Large ECochG amplitude drops observed during electrode insertion indicated poorer hearing preservation. Although the outcomes were variable, this information may be helpful to guide surgical decision-making when contemplating full electrode insertion and the likelihood of hearing preservation.